2021
DOI: 10.3390/mi12030328
|View full text |Cite
|
Sign up to set email alerts
|

Retention Enhancement in Low Power NOR Flash Array with High-κ–Based Charge-Trapping Memory by Utilizing High Permittivity and High Bandgap of Aluminum Oxide

Abstract: For improving retention characteristics in the NOR flash array, aluminum oxide (Al2O3, alumina) is utilized and incorporated as a tunneling layer. The proposed tunneling layers consist of SiO2/Al2O3/SiO2, which take advantage of higher permittivity and higher bandgap of Al2O3 compared to SiO2 and silicon nitride (Si3N4). By adopting the proposed tunneling layers in the NOR flash array, the threshold voltage window after 10 years from programming and erasing (P/E) was improved from 0.57 V to 4.57 V. In order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The electron dispersive spectroscopy (EDS) line scans below the TEM images also indicate minimal atomic/interfacial changes. It has been demonstrated that CTM cells exhibit charge retention times over 10 years [92][93][94] . = 1.6, 6.2, 0.25, 29.8 pm, respectively.…”
Section: Charge Trap Memory Experimental Demonstrationmentioning
confidence: 99%
“…The electron dispersive spectroscopy (EDS) line scans below the TEM images also indicate minimal atomic/interfacial changes. It has been demonstrated that CTM cells exhibit charge retention times over 10 years [92][93][94] . = 1.6, 6.2, 0.25, 29.8 pm, respectively.…”
Section: Charge Trap Memory Experimental Demonstrationmentioning
confidence: 99%
“…These authors also suggested [50] short O 3 treatment of Si to obtain better Al 2 O 3 /Si interfacial properties. Improvement of retention by the engineering of tunnelling oxide is suggested in the work of Song et al [64]. They demonstrated by using Synopsis simulations that incorporation of Al 2 O 3 in the tunnelling oxide (i.e., SiO 2 /Al 2 O 3 /SiO 2 stack) results in a significant improvement in retention.…”
Section: Tunneling and Blocking Oxidesmentioning
confidence: 99%
“…This Special Issue provides insight on and advancements in Flash memory devices. There are nine papers including one review paper, covering the reliability of 3D NAND Flash devices [1][2][3], the characterization and design of Flash memory cell/string [2,4,5], NOR Flash memories for embedded applications [5], a set of Error Correction Codes and Secondary Correction Algorithms for flash memories [6,7], Flash management through flash signal processing in controllers for Big Data storage [6][7][8], and the impact of Flash memories on Solid State Drives reliability and performance [8,9].…”
mentioning
confidence: 99%
“…Moreover, under scaled cell dimensions, the improvement becomes protruding. In [5], Song et al incorporated aluminum oxide in tunnel oxide to improve retention characteristics of NOR flash arrays. By adopting the proposed tunneling layers in the NOR flash array, the threshold voltage window after 10 years from programming and erasing (P/E) was improved by 4 V. The validation of the proposed device structure took place by comparing it with another stacked-engineered structure with SiO 2 /Si 3 N 4 /SiO 2 tunneling layers.…”
mentioning
confidence: 99%